2020
DOI: 10.1016/j.enpol.2020.111760
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking electric vehicle subsidies, rediscovering energy efficiency

Abstract: Existing regulations regarding fuel energy intensity (MJ/km, litres/100 km, or its inverse, miles per gallon) of light-duty vehicles (LDVs: cars, SUVs, and pickup trucks) for 2025 or 2030 either fall short of the longterm technical potential, or contain numerous loopholes that undermine their effectiveness. At the same time, governments are subsidizing the purchase of electric vehicles (EVs) while the market share of SUVs and pickup trucks grows. This paper reviews the feasible fuel and/or electricity energy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Nagy, Hagspiel, and Kort found that the government should reduce the risk of subsidy withdrawal as much as possible from the perspective of social welfare (Li et al, 2020;Hagspiel et al, 2021;Nagy et al, 2021;Yang et al, 2021). Harvey et al found that the government should cut or stop electric vehicle subsidies for environmental benefits (Harvey, 2020). Deng and Tian found that avoiding excessive subsidies can prevent NEV manufacturers from defrauding the government to obtain grants (Deng and Tian, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nagy, Hagspiel, and Kort found that the government should reduce the risk of subsidy withdrawal as much as possible from the perspective of social welfare (Li et al, 2020;Hagspiel et al, 2021;Nagy et al, 2021;Yang et al, 2021). Harvey et al found that the government should cut or stop electric vehicle subsidies for environmental benefits (Harvey, 2020). Deng and Tian found that avoiding excessive subsidies can prevent NEV manufacturers from defrauding the government to obtain grants (Deng and Tian, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hybrid vehicles, such as the Hybrid Electric Vehicle (HEV) and the Plug-In Hybrid Electric Vehicle (PHEV), can be a transitional period for Indonesia to face vehicle electrification. Bob Azam from Toyota Motor Manufacturing Indonesia stated that this hybrid car could popularize environmentally friendly vehicles and are more affordable than BEVs (Indra, 2019). Based on research conducted by the Lembaga Penyelidikan Ekonomi dan Masyarakat Universitas Indonesia, respondents are still worried about BEV's technical problems such as how to charge when the battery runs out.…”
Section: Introductionmentioning
confidence: 99%